2017
DOI: 10.1002/dmrr.2897
|View full text |Cite
|
Sign up to set email alerts
|

Lixisenatide as add‐on treatment among patients with different β‐cell function levels as assessed by HOMA‐β index

Abstract: BackgroundThe effect of lixisenatide—a prandial once‐daily glucagon‐like peptide‐1 receptor agonist—on glycaemic control in patients with inadequately controlled type 2 diabetes mellitus (T2DM), stratified by baseline β‐cell function, was assessed.MethodsThe 24‐week GetGoal‐M, ‐P and ‐S trials evaluated the efficacy and safety of lixisenatide in combination with oral antidiabetic agents. This post hoc analysis used data from patients receiving lixisenatide in these trials, divided into matched cohorts by prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…As a consequence, short-acting GLP-1 RAs exert a greater postprandial effect than long-acting GLP-1 RAs [5] and may provide a mechanism of glucose lowering independent of b-cell function that might be relevant to patients with longstanding diabetes. A previous post hoc analysis found results consistent with the current study, in that the effects of lixisenatide were consistent across patients with varying levels of b-cell function [14].…”
Section: Discussionsupporting
confidence: 91%
“…As a consequence, short-acting GLP-1 RAs exert a greater postprandial effect than long-acting GLP-1 RAs [5] and may provide a mechanism of glucose lowering independent of b-cell function that might be relevant to patients with longstanding diabetes. A previous post hoc analysis found results consistent with the current study, in that the effects of lixisenatide were consistent across patients with varying levels of b-cell function [14].…”
Section: Discussionsupporting
confidence: 91%
“…Conflicting results have been reported as to whether or not beta‐cell function affects the glycaemic response to GLP‐1RAs. A recent study which also used HOMA2‐%B measurements showed similar reductions in HbA1c with once‐daily lixisenatide in patients with low HOMA2‐%B as those with less deteriorated beta‐cell function, suggesting the presence of sufficient beta‐cell function that could still respond to stimulation by GLP‐1RAs. Nonetheless, the absolute residual beta‐cell capacity may be key in determining the response to GLP‐1RAs.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, in an observational study, patients with a lower urinary C‐peptide creatinine ratio were associated with reduced glycaemic response to liraglutide . In contrast, lixisenatide improved glycaemic control irrespective of beta‐cell function, as measured by the secretory units of islets in transplantation index and by homeostatic model assessment for beta‐cell function, HOMA2‐%B . In comparison to reduced glycaemic response to GLP‐1RA therapies in patients with islet autoantibodies, in a condition frequently called latent autoimmune diabetes in the adult (LADA), characterised by impaired beta‐cell function—dulaglutide appears to remain effective .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced endogenous insulin secretion was defined as meeting two or more of the following requirements: homeostatic model assessment (HOMA)-β of <30%, 16,17 C-peptide index (CPI) of <0.7, 18,19 and the difference in glucagon loading test between the C-peptide immunoreactivity (CPR) values at 0 min and 6 min (ΔCPR) of <0.1 (ng/mL) [CPR 6 min after intravenous injection of glucagon (CPR-6 min), increment of CPR (ΔCPR)]. 14,20,21 However, all the subjects in our study showed fasting immunoreactive insulin (IRI) and fasting CPR below measurement sensitivity in a test performed on initiation of insulin.…”
Section: Study Subjectsmentioning
confidence: 99%